Achromatopsia: Case Presentation and Literature Review Emphasising the Importance of Genetic Testing for Disease Diagnosis, Management and Prenatal Diagnosis - Kumari Pritti; Vineet Mishra; Udhaya Kotecha; Somesh Aggarwal (Advanced Concepts in Medicine and Medical Research Vol. 9, 2023)
This chapter reports the cases of two siblings (8 and 5 years old) who were diagnosed with achromatopsia after genetic analysis. Achromatopsia (rod monochromatism) is a rare autosomal recessive form of cone dysfunction that is characterized by a near normal fundus appearance, nystagmus, a nonrecordable photopic ERG, and normal to near normal scotopic ERG that remains stable. The genetic approach for these patients is currently an important issue, and gene therapy is an ongoing therapeutic option already being studied in clinical trials. We report the case of two siblings (8 and 5 years old) affected by achromatopsia. They carry compound heterozygous mutations in the CNGA3 gene at positions 1306 and 1279 in exon 8 (c.136C> T, p.Arg436Trp and c.1279C> T, p.Arg427Cys). Genetic testing is crucial to confirm the diagnosis in such cases. Molecular genetic testing approaches that can be considered include targeted analysis for common variants, the use of a multigene panel, or comprehensive genomic testing, typically exome sequencing. The parents were found to have one of the variants in a heterozygous condition. This is the first reported case of achromatopsia in India. This report highlights the significance of genetic testing even more. It emphasizes that exome sequencing is a better diagnostic strategy when paired with standard testing, especially for disorders like achromatopsia and others where misdiagnosis might occur from depending only on clinical examinations.